2006
DOI: 10.1063/1.2205849
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer processes on Ag and Au clusters supported on TiO2(110) and cluster size effects

Abstract: The results of a detailed study of Li(+) neutralization in scattering on Ag and Au clusters and thin films supported on TiO(2) are presented. A very efficient neutralization is observed on small clusters with a decrease for the smallest clusters. These results closely follow the size-effects observed in the reactivity of these systems. The energy dependence of the neutralization was studied for the larger clusters (>4 nm) and observed to be similar in trend to the one observed on films and bulk (111) crystals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…To study the effects of roughness, a clean polycrystalline Au foil was sputtered with Ar under the same experimental conditions used for sputtering the Au film on TiO 2 , but no concurrent changes in the scattered alkali-metal ion neutralization were observed. It was also previously observed that Ar sputtering of a Au foil [13] and Au(111) [15] does not change the surface work function or increase the neutralization during alkali-metal ion scattering. Therefore, the increase of NF with sputtering of Au clusters on TiO 2 cannot be explained simply by a change of surface roughness.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…To study the effects of roughness, a clean polycrystalline Au foil was sputtered with Ar under the same experimental conditions used for sputtering the Au film on TiO 2 , but no concurrent changes in the scattered alkali-metal ion neutralization were observed. It was also previously observed that Ar sputtering of a Au foil [13] and Au(111) [15] does not change the surface work function or increase the neutralization during alkali-metal ion scattering. Therefore, the increase of NF with sputtering of Au clusters on TiO 2 cannot be explained simply by a change of surface roughness.…”
mentioning
confidence: 81%
“…The energy of the scattered projectile can be used to separate the signal from the nanocluster from that of the support. This technique has recently been able to detect the confined states of vapor deposited Au [13,14] and Ag [15] nanoclusters.…”
mentioning
confidence: 98%
“…Thus scattering on clusters and monolayer thin films has attracted attention [24][25][26]. Experimental studies of alkalimetal neutralization on supported Ag and Au clusters were performed [24,25] in the quest of observation of quantum-size effects [27][28][29], and showed that alkali-metal neutralization proceeds much more efficiently on small clusters than on films or bulk metal surfaces. Recent theory has also addressed the case of electron transfer on ultrathin films [30,31] and the effect of quantization because of the finite thickness of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electron exchange in nanosystems also exhibits such interesting phenomena as quantum-size effects [16,17,18,19,20] and quantum vortices [21].…”
Section: Introductionmentioning
confidence: 99%